THE ROLE OF ENGLISH IN THE DIGITAL AGE - Eshqobilova Shohsanam Azamat qizi, (TADQIQOTLAR, 2026)
Abstract The  rapid  development  of  digital  technologies  has  significantly  changed  the structure of modern society, influencing education, communication, economics, and professional activities. In this context, the English language has become a key element of global digital interaction. This article examines the role of English in the Digital Age, emphasizing its importance in information technologies, digital education, online communication, and professional competence development. The study also discusses the pedagogical implications of teaching English in technologically advanced learning environments.